Analytical, Numerical, and Experimental Analysis of Tangential Attraction and Repulsion Forces Between Parallel Magnets in an Automotive Mechanical System - Carmelo Serraino; Tommaso Carditello; Luca Dusini; Alberto Nicoletta; Dario Santonocito; Giacomo Risitano (Engineering Proceedings)
This study highlights the importance of magnets in the advancement of automotive technology, focusing on the forces of attraction and repulsion between two magnets in relative tangential motion. The magnets were tested using a tensile machine developed by KnoWow and adapted to measure attraction forces as a function of longitudinal and transversal distances. The data collected made it possible to create a detailed map of the interactions of the forces. To validate the experimental results, a finite element analysis (FEA) was performed. The high correspondence between the experimental and simulated data confirmed the reliability of the method, making it usable for future automotive designs requiring optimization of magnetic forces.